Successful Management of Unexpected Massive Blood Loss during Robot-assisted Partial Nephrectomy: A Case Report - Sandip Baheti; Prashant Sakhavalkar; Runjhun Jain; Utkarshini Kedia; M Sharan (Journal of Clinical and Diagnostic Research)
Robot-assisted Partial Nephrectomy (RAPN) for Renal Cell Carcinoma (RCC) is a minimally invasive surgery with reconstructive potential. Due to the high vascularity associated with RCC and the steep learning curve of robotic surgery, the risk of vascular injury is elevated. Authors hereby, report a case of a 50-year-old female scheduled for RAPN, which was later converted to open nephrectomy. During the surgery, there was an accidental massive haemorrhage and hypotension due to a sudden iatrogenic rupture of the Inferior Vena Cava (IVC). Although two units of Packed Cell Volume (PCV) and Fresh Frozen Plasma (FFP) had been reserved, massive haemorrhage and hypotension occurred suddenly, and as the blood bank was not in the same building, blood was not readily available. Additionally, managing the massive haemorrhage and hypotension was challenging due to spatial restrictions and the difficulty in accurately judging blood loss during robotic surgery. To maintain cerebral circulation, a head-down position with a left tilt was useful, as this positioned the heart at its most dependent position for maximum venous drainage. To save time and avoid delays in resuscitation authors implemented their implemented our Contact-Act-Coordinate-Correlate (CACC) protocol alongside clinical guidelines. The importance of prompt action and aggressive fluid transfusion until blood became available cannot be overstated; it is crucial not to wait for ideal fluids if they are not readily available, as maintaining microcirculation is a priority. Moreover, frequent laboratory investigations and correlation should not be neglected. However minimally invasive the surgery may be, prior blood grouping and cross-matching are essential for managing unexpected bleeding complications during such procedures.